Social Comparison as a Moderator between Perceived Social Risk and Purchase Intention - Michniuk, Agnieszka; Gansser, Oliver; Schmitz, Sven Olaf (Communication Today, 2025)
The study aims to analyse the moderator effect of social comparison, which influences the strength of the relationship between perceived social risk (independent variable) and purchase intention (dependent variable). Next to that, it aims to answer the question whether there are any differences in the effects of trust and perceived social risk on the intention to join a fitness centre when participants are exposed to advertising which depicts a slim model (desired end state) or to advertising portraying a heavy one (undesired end state). The results show that, on the one hand, social comparison influences the strength of the effect of perceived social risk on the intention to join a fitness centre. On the other hand, there is a significant difference and a higher influence of perceived social risk on the intention to join a fitness centre when participants are exposed to a desired end state via advertising.